Impact of Microfinance on Socio-Economic Conditions of the Borrowers: A Case Study of Akhuwat Foundation (Lahore) - Zaidi, Hassan Hamza (European Journal of Multidisciplinary Studies, 2017)
Akhuwat Foundation is the leading microfinance institution in Pakistan which provides interest free loans for small businesses to the poorest people of society. Since its launch in 2001, it has disbursed a sum of -110 million to 1.9 million families without any collateral and with a recovery rate of 99.93 percent. Such a remarkable achievements by a nonprofit organization makes it a leading interest free (Qarze e Hasna) institution in the world. This study attempts to find the impact of Akhuwat Foundation’s microfinance on socio-economic conditions of the borrowers. Based on primary data collected from old and new borrowers, the study analyzes the impact of microfinance on wellbeing of the borrowers’ households in terms of their housing conditions, food security, children’s education, poverty status, monthly income and expenditures of the borrowers before and after the loan with the help “with or without approach”. Moreover, a non-parametric approach is used to test the difference between old and new borrowers in terms of their consumption expenditure, income, poverty status, housing improvement, access to education, and access to medical facilities. Our results show that Akhuwat’s loans have significantly improved the conditions of the borrowers in terms of their monthly income, expenditures, access to education/ health, and household assets. The impact was much larger for old borrowers than new borrowers. In the end we concluded that Akhuwat’s non-traditional approach of lending to the poor and its model of mutual brotherhood between lenders and borrowers presents great lessons to bring positive change in the society.